Enhancing Brand Image through Product Quality, Price Perception, Innovation, and Word of Mouth - Ferdiansyah, Ferdiansyah; Diposumarto, Ngadino Surip; Muharram, Hari (LifeSciFi, 2025)
This study aims to analyze the effects of product quality, price perception, product innovation, and Word of Mouth (WOM) on the brand image of Wuling cars in Province B. It employs a quantitative descriptive method, with data analysis tailored to the research pattern and variables studied, using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The results indicate that all proposed hypotheses are accepted. Product quality significantly influences WOM, with attractive car design as the main indicator, supported by promotional strategies such as discounts. The perception that price aligns with product benefits also enhances WOM, particularly through well-structured discount strategies. Product innovation, including the development of new car models, significantly drives positive WOM, further strengthening Wuling's brand image. Moreover, WOM plays a crucial mediating role in the relationship between product quality, price perception, product innovation, and brand image. In the context of brand image, attractive car design is the primary element that creates a positive impression among consumers. This study makes a valuable contribution to marketing literature by integrating five key variables into a comprehensive analytical framework. Practical implications include a focus on product innovation, competitive pricing strategies, and leveraging WOM to enhance brand positioning in the automotive market.